2020
DOI: 10.1093/milmed/usaa157
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements: Knowledge and Adverse Event Reporting Practices of Department of Defense Health Care Providers

Abstract: Introduction The purpose of the study was to assess the knowledge of dietary supplements (DS) and adverse event (AE) reporting practices of the Department of Defense health care providers. AEs related to use of DS are not uncommon. However, it is estimated that less than 2% of AEs are reported. This is problematic given the Food and Drug Administration relies on AE reports to identify and ultimately remove unsafe products from the market. Inadequate reporting of AE puts all DS users at risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Similarly, 88.9% of the dietitians believed the positive relationship between adequate-balanced nutrition and the course of COVID-19 in a study (32). Studies reported that health professionals had low to moderate knowledge about DS/HF, and they may need additional education on DS/HF use (28, 31,33,34). Our study showed that the total knowledge scores of health professionals were 3.85 ± 1.60 and increased to 5.51 ± 1.45 signi cantly after education (p = 0.000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, 88.9% of the dietitians believed the positive relationship between adequate-balanced nutrition and the course of COVID-19 in a study (32). Studies reported that health professionals had low to moderate knowledge about DS/HF, and they may need additional education on DS/HF use (28, 31,33,34). Our study showed that the total knowledge scores of health professionals were 3.85 ± 1.60 and increased to 5.51 ± 1.45 signi cantly after education (p = 0.000).…”
Section: Discussionmentioning
confidence: 99%
“…Although DS/HF are widely recommended during COVID-19 pandemic, studies showed that health professionals may not be adequately informed about their use (28)(29)(30). Therefore, it is vital to provide additional training or information to health professionals on DS/HF use (31). Studies about health professionals' knowledge on DS/HF during the COVID-19 pandemic are limited however, one study reported that 94.5% of the dietitians used DS, and 46.1% used HF for the prevention of COVID-19 (32).…”
Section: Introductionmentioning
confidence: 99%
“…Published reports indicate that 60% to 81% of HCPs have encountered an AE in association with a DS. [20][21][22] Despite observing such events, most HCPs report lacking the knowledge as to where and how to report such AE. [20][21][22] Interestingly, many do report the observed AE (10%-41%), but to various sources, including the hospital database, other specialists, Poison Control Center, and the like.…”
Section: Gaps In Ae Reporting That Need To Be Filledmentioning
confidence: 99%
“…[20][21][22] Despite observing such events, most HCPs report lacking the knowledge as to where and how to report such AE. [20][21][22] Interestingly, many do report the observed AE (10%-41%), but to various sources, including the hospital database, other specialists, Poison Control Center, and the like. The FDA's Safety Reporting Portal is intended to streamline the process of reporting product safety issues to the FDA and the National Institutes of Health.…”
Section: Gaps In Ae Reporting That Need To Be Filledmentioning
confidence: 99%
See 1 more Smart Citation